Immunostimulant Effect of Garlic Chives Leaf Ethanolic Extract (Allium tuberosum) by Increasing Level of Antioxidant at Rats Doxorubicin-Induced Rats - Ika Rahmawati Sutejo; Kiky Martha Ariesaka; Fuad Adi Prasetyo; Mudzakkir Taufiqurrqhman; Ain Yuanita Insani; Brilliant Givya Ariansari (Indonesian Society for Cancer Chemoprevention, 2016)
Cancer is one of the leading causes of death in the world, approximately 14 million new cases and 8.2 million deaths each year. Doxorubicin is a well-known chemotherapy drug which frequently used in treating various types of cancer. However, doxorubicin posesses several side effects including cardiotoxic, hepatotoxic, nephrotoxic, and immunosuppression. One of the natural product that can be used as an adjuvant of doxorubicin to reduce the toxic effects is garlic chives (Allium tuberosum). The purpose of this study was to determine the effect of Allium tuberosum based on hematological profile, levels of CD4+, CD8+, and MDA serum of male Wistar rats which induced by doxorubicin. The hematological profile was analyzes by blood smear, levels of CD4+ and CD8+ were conducted by flowcytometry and levels of MDA serum were determined by spectrofotometry. The results showed that the etanolic extract of Allium tuberosum (EAT) increased neutrophil and lymphocyte, percentage of CD4+ cells (p<0.01) and CD8+ cells. It also decreased the levels of serum MDA (p<0.01). These results indicated that EAT work as immunostimulant possibly through an antioxidant mechanism (MDA). It can be concluded that EAT can be developed as adjuvant for doxorubicin.Keywords: doxorubicin, Allium tuberosum, immunostimulant, antioxidant, CD4+, CD8+